(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
In this interview, Valmir Perez talks about how he began his career in Lighting and what happened in his professional trajectory of more than 30 years of experience. He also talks about his work as the lighting designer responsible for Unicamp’s Lighting Laboratory. The artist reflects on the importance of the scenic lighting professional within the university, regarding the development of university lighting laboratories and the support to the formation of Theater and Dance undergrade students. In addition, Valmir Perez express his desire to standardize the documentation of stage lighting creations in Brazil.